UNIT 9B.3 A Mouse Model of Foodborne Listeria monocytogenes Infection. Issue 1 (5th November 2013) - Bou Ghanem, Elsa N.; Myers‐Morales, Tanya; D'Orazio, Sarah E.F.
Abstract: Listeria monocytogenes causes foodborne disease in humans that ranges in severity from mild, self‐limiting gastroenteritis to life‐threatening systemic infections of the blood, brain, or placenta. The most commonly used animal model of listeriosis is intravenous infection of mice. This systemic model is highly reproducible, and thus, useful for studying cell‐mediated immune responses against an intracellular bacterial pathogen, but it completely bypasses the gastrointestinal phase of L. monocytogenes infection. Intragastric inoculation of L. monocytogenes produces more variable results and may cause direct bloodstream invasion in some animals. The foodborne transmission model described here does not require specialized skills to perform and results in infections that more closely mimic human disease. This natural feeding model can be used to study both the host‐ and pathogen‐derived factors that govern susceptibility or resistance to orally acquired L. monocytogenes . Curr. Protoc. Microbiol . 31:9B.3.1‐9B.3.16. © 2013 by John Wiley & Sons, Inc.